ENVIRONMENTAL LITERACY PROFILE OF STUDENTS IN NATURAL SCIENCE LEARNING-BASED EXPERIENTIAL - Yasaroh, Sabila; Wilujeng, Insih; Atun, Sri; Indah Puspita Sari, Mega (Universitas Tanjungpura, 2023)
The issue of environmental damage has been widely discussed in recent years in various parts of the world. Environmental literacy is very necessary for the prevention of environmental problems and for creating a healthy environment. One effective model to improve environmental literacy in schools is Experiential Learning, which invites students to design actions to care for the environment and actively participate in providing solutions to environmental problems. This study aims to determine the environmental literacy profile of students at SMPN 4 Depok in experiential learning-based science learning. This research is a quantitative descriptive study with a cluster random sampling technique, namely 50 students of classes VIIA and VII C. The data collection instrument used was 7 environmental literacy description test questions developed from 4 environmental literacy indicators (knowledge, attitudes, skills, and behavior). Data analysis was carried out quantitatively by calculating the percentage to determine the category of students' environmental literacy. Based on the results of data analysis, it was found that the average achievement of the knowledge aspect was 86.2%; the attitude aspect is 65.5%; the skill aspect is 82.5%, and the behavioral aspect is 71.4%. The average of these results shows the level of environmental literacy is 76.4% which is included in the high category. After knowing the environmental literacy profile of students, it is necessary to develop research on interesting and innovative media in science learning so that the four stages of Experiential Learning can run more optimally.